EMOTIONAL ALIENATION IN ADOLESCENTS: AFFECTIVE DISTANCING IN TIMES OF HYPERCONNECTIVITY (PRÁXIS EM SAÚDE, 2026)
This article aims to analyze the impacts of social media on the emotional development and affective bonds of adolescents, reflecting on how hyperconnectivity interferes with identity construction and interpersonal relationships. This is a theoretical-reflective study, based on a review of contemporary literature addressing the psychological and social aspects of juvenile behavior in the digital era. The analysis discusses how the virtual environment, while expanding possibilities for expression and belonging, also contributes to the weakening of affective bonds and the superficialization of social interactions. It was observed that excessive use of social media can lead to emotional isolation, dependence on external validation, and difficulties in empathic communication, compromising the quality of relationships and the development of a solid identity. It is concluded that understanding these phenomena is essential for psychology professionals and students to develop sensitive listening skills and intervention strategies aimed at the conscious use of technology, strengthening human contact and the emotional health of young people. Thus, a necessary reflection is proposed: how to promote genuine and balanced affective bonds in a generation that is increasingly connected, yet emotionally distant?
Keywords: Adolescence; Social media; Affectivity; Behaviour; Hyperconnectivity